Preparation method and application of ultrathin bismuth vanadate nanosheet photocatalyst

The ultrathin bismuth vanadate nanosheet photocatalyst was synthesized by hydrothermal method, which solved the problem of high photogenerated carrier recombination rate of bismuth vanadate photocatalyst, achieved efficient degradation of antibiotics, and improved catalytic activity and degradation effect.

CN119114052APending Publication Date: 2024-12-13ANQING NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411274455.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The photogenerated carrier recombination rate of pure bismuth vanadate photocatalysts is too high during the photocatalysis process, which limits the full use of their photocatalytic activity and makes it difficult to effectively degrade antibiotics.

Method used

The ultrathin bismuth vanadate nanosheet photocatalyst was synthesized by one-step hydrothermal method, and prepared by heating treatment in an autoclave and magnetic stirring, which significantly reduced the photogenerated carrier recombination rate of the material and improved its degradation of antibiotics. efficiency.

Benefits of technology

The photocatalytic activity of bismuth vanadate photocatalyst is improved, and the degradation efficiency of antibiotics is significantly improved. The degradation of antibiotics is wide, with simple methods and mild reaction conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119114052A_ABST
    Figure CN119114052A_ABST
Patent Text Reader

Abstract

The invention is applicable to the technical field of pharmaceutical wastewater treatment, and provides a preparation method and application of an ultrathin bismuth vanadate nanosheet photocatalyst, and the method comprises the following steps: step 1, preparing an ultrathin bismuth vanadate nanosheet precursor material; and step 2, preparing the ultrathin bismuth vanadate nanosheet photocatalyst. The ultrathin bismuth vanadate nanosheet photocatalyst is applied to efficient degradation of antibiotics in water. The ultrathin bismuth vanadate nanosheet photocatalyst prepared by the preparation method disclosed by the invention is relatively pure in phase, simple in preparation method, mild in reaction condition, efficient in antibiotic degradation performance and wide in antibiotic degradation variety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of pharmaceutical wastewater treatment, and in particular relates to a preparation method and application of an ultra-thin bismuth vanadate nanosheet photocatalyst. Background Art

[0003] Traditional wastewater treatment methods, such as biological and physical methods, are often incapable of dealing with antibiotics and are easily restricted by conditions such as temperature and pH, making it difficult to achieve ideal purification effects. In contrast, advanced oxidation technologies in chemical methods, especially emerging methods such as photocatalysis, ozone oxidation, and persulfate oxidation, have shown great potential. Among them, photocatalytic technology stands out for its economy and efficiency. It uses semiconductor photocatalytic materials to capture solar energy, excite electron-hole pairs, and then drive the redox decomposition of organic pollutants to achieve water purification. However, photocatalytic technology also faces challenges: the rapid recombination of electron-hole pairs inside semiconductor materials seriously restricts the utilization efficiency of photogenerated carriers, thereby affecting the degradation efficiency.

[0004] To overcome this bottleneck, researchers are actively exploring new photocatalytic materials, among which bismuth vanadate (BiVO4) stands out among many candidate materials for its unique energy band structure, environmental friendliness, cost-effectiveness and excellent visible light absorption ability, becoming a new favorite in the fields of photocatalysis, electrocatalysis and energy storage. Despite this, pure BiVO4 photocatalyst still has the problem of too high recombination rate of photogenerated carriers, which limits its full photocatalytic activity.

[0005] In view of this, developing a simple and fast synthesis strategy to prepare high-performance BiVO4 photocatalytic materials to significantly improve their degradation efficiency of antibiotics has become an urgent need in current research. Summary of the invention

[0006] The purpose of the present invention is to provide a preparation method and application of ultrathin bismuth vanadate nanosheet photocatalyst, aiming to solve the problems mentioned in the above background technology.

[0007] The present invention is achieved by a method for preparing an ultrathin bismuth vanadate nanosheet photocatalyst, comprising the following steps:

[0008] Step 1: Preparation of ultrathin bismuth vanadate nanosheet precursor material

[0009] Bismuth chloride (BiCl3) is added into a beaker containing a certain volume of water-ethylene glycol mixed solution, and then a certain amount of surfactant is added into the beaker, and stirred at room temperature with a magnetic stirrer to dissolve it;

[0010] Then, a certain amount of sodium orthovanadate dodecahydrate (NaVO4·12H2O) was added to the beaker and stirred to obtain a bright yellow mixed precursor solution;

[0011] Step 2: Preparation of ultrathin bismuth vanadate nanosheet photocatalyst

[0012] The bright yellow mixed precursor solution obtained in step 1 is transferred into a high-pressure reactor, and then the temperature is raised to a certain temperature in the high-pressure reactor, and the temperature is kept constant for a period of time;

[0013] Finally, the ultrathin bismuth vanadate nanosheet photocatalyst was obtained by naturally cooling to room temperature, washing and drying.

[0014] A further technical solution is as follows: in step 1, in the water-ethylene glycol mixed solution, the volume ratio of water to ethylene glycol is 1:1-4; the surfactant is cetyltrimethylammonium bromide (CTAB); the molar ratio of bismuth chloride (BiCl3) to the surfactant is 1:0.4-4; and a magnetic stirrer is used to stir at room temperature for 40 minutes to dissolve it.

[0015] A further technical solution is that in step 1, the molar ratio of sodium orthovanadate dodecahydrate (NaVO4·12H2O) to bismuth chloride (BiCl3) is 1:1; stirring for 30 minutes obtains a bright yellow mixed precursor solution.

[0016] According to a further technical solution, in step 2, the treatment temperature in the high-pressure reactor is 100 to 200° C., and the constant temperature treatment time is 2 to 24 hours.

[0017] According to a further technical solution, the treatment temperature in the high-pressure reactor is 120° C. and the constant temperature treatment time is 6 hours.

[0018] According to a further technical solution, in step 2, the washing refers to washing the product with deionized water and ethanol for multiple times.

[0019] According to a further technical solution, in step 2, the drying refers to vacuum drying at a temperature of 60° C. to obtain an ultrathin bismuth vanadate nanosheet photocatalyst.

[0020] Another object of the present invention is to provide an application of an ultrathin bismuth vanadate nanosheet photocatalyst, wherein the ultrathin bismuth vanadate nanosheet photocatalyst is prepared by the above-mentioned preparation method of the ultrathin bismuth vanadate nanosheet photocatalyst, and the application is the application of the ultrathin bismuth vanadate nanosheet photocatalyst in the efficient degradation of antibiotics in water, comprising the following steps:

[0021] Step a, adding a certain mass of ultrathin bismuth vanadate nanosheet photocatalyst to a certain concentration of antibiotics, and leaving it in a dark place for a period of time;

[0022] Step b, then put it on a magnetic stirrer and use a 300W xenon lamp as a light source to carry out a photocatalytic experiment, take out the fixed solution at regular intervals, measure the absorbance of the upper clear liquid obtained after centrifugation, and calculate its removal rate.

[0023] A further technical solution is that in step a, the standing time in the dark is 30 minutes; the dosage of the ultrathin bismuth vanadate nanosheet photocatalyst is 0-4 g / L; the antibiotic is one or more combinations of oxytetracycline, ceftazidime, doxorubicin hydrochloride, sulfamethoxazole, chlortetracycline hydrochloride and tetracycline hydrochloride, and the concentration of the antibiotic is 5-100 mg / L.

[0024] In a further technical solution, in step b, a photocatalytic experiment is carried out under constant temperature conditions using a 700 rpm (revolutions / minute) magnetic stirrer and a 300W xenon lamp as a light source, the stirring time is 120 min, and the light intensity is 30-100 mW / cm 2 ; Take 3.5mL of solution at regular intervals.

[0025] The preparation method and application of an ultrathin bismuth vanadate nanosheet photocatalyst provided by the present invention have the following beneficial effects:

[0026] Ultrathin bismuth vanadate nanosheet photocatalysts were synthesized in one step by a hydrothermal method. The material phase was relatively pure, the method was simple, and the reaction conditions were mild. Subsequently, under stirring, a xenon lamp provided a light source to investigate the degradation of antibiotics in water under illumination, and the photocatalytic effect under light conditions was investigated. It was found that the morphology of bismuth vanadate catalysts synthesized by different methods significantly affected their catalytic effects. The ultrathin bismuth vanadate nanosheet photocatalysts obtained by the present invention had high efficiency in degrading antibiotics and could degrade a wide range of antibiotics. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 is the XRD pattern of the bismuth vanadate catalyst synthesized in Example 1;

[0028] Figure 2 TEM image of the ultrathin bismuth vanadate nanosheet in Example 1;

[0029] Figure 3 is an AFM image of the ultrathin bismuth vanadate nanosheet in Example 1;

[0030] Figure 4 is the SEM image of Example 1;

[0031] Figure 5 It is the SEM image of comparative example 1 in embodiment 1;

[0032] Figure 6 It is the SEM image of comparative example 2 in embodiment 1;

[0033] Figure 7It is the SEM image of comparative example 3 in Example 1;

[0034] Figure 8 The degradation diagram of Example 2 and oxytetracycline hydrochloride of different concentrations;

[0035] Fig. 9 The graphs are the degradation of Example 2 and Comparative Examples 1, 2 and 3 to 60 mg / L oxytetracycline hydrochloride. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0037] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.

[0038] Example 1

[0039] like Figure 1-7 As shown, a method for preparing an ultrathin bismuth vanadate nanosheet photocatalyst provided by an embodiment of the present invention is prepared by a hydrothermal method, comprising the following steps:

[0040] 1) Add 2.21 g BiCl3 into a beaker containing 60 mL of a 1:1 volume ratio water-ethylene glycol solution and stir it magnetically to completely dissolve it. Then add 1.05 g CTAB and stir it for 40 min to completely dissolve it to obtain a transparent and clear solution.

[0041] 2) adding 2.80 g of NaVO4·12H2O to the solution obtained in step 1) under stirring conditions, and magnetically stirring for 30 min to obtain a bright yellow mixed precursor solution;

[0042] 3) transferring the solution obtained in step 2) into a reaction vessel and treating at 120° C. for 6 h to obtain a yellow solid product;

[0043] 4) The yellow solid product obtained in step 3) was washed with deionized water and ethanol for multiple times, and then vacuum dried at 60° C. for 12 h to obtain an ultrathin bismuth vanadate nanosheet catalyst.

[0044] The TEM, AFM, XRD and SEM images of the ultrathin bismuth vanadate nanosheet catalyst in Example 1 are as follows: Figure 1 , 2 , 3 and 4.

[0045] Comparative Example 1 of Example 1

[0046] An embodiment of the present invention provides a method for preparing an ultrathin bismuth vanadate nanosheet photocatalyst, which is prepared by a hydrothermal method, wherein the hydrothermal temperature is 120° C. and the reaction time is 12 hours, and the method comprises the following steps:

[0047] 1) Add 2.21 g BiCl3 into a beaker containing 60 mL of water and ethylene glycol, stir magnetically to dissolve it completely, then add 1.05 g CTAB and stir for 40 min to dissolve it completely to obtain a transparent and clear solution;

[0048] 2) adding 2.80 g of NaVO4·12H2O to the solution obtained in step 1) under stirring conditions, and magnetically stirring for 30 min to obtain a bright yellow mixed precursor solution;

[0049] 3) transferring the solution obtained in step 2) into a reaction vessel and treating at 120° C. for 12 h to obtain a yellow solid product;

[0050] 4) The yellow solid product obtained in step 3) was washed with deionized water and ethanol for multiple times, and then vacuum dried at 60° C. for 12 h to obtain an ultrathin bismuth vanadate nanosheet catalyst.

[0051] Comparative Example 2 of Example 1

[0052] An embodiment of the present invention provides a method for preparing an ultrathin bismuth vanadate nanosheet photocatalyst, which is prepared by a hydrothermal method, wherein the hydrothermal temperature is 120° C. and the reaction time is 24 hours, and comprises the following steps:

[0053] 1) Add 2.21 g BiCl 3 into a beaker containing 60 mL of water and ethylene glycol, stir it with a magnetic stirrer to completely dissolve it, then add 1.05 g CTAB and stir it for 40 min to completely dissolve it, to obtain a transparent and clear solution;

[0054] 2) adding 2.80 g of NaVO4·12H2O to the solution obtained in step 1) under stirring conditions, and magnetically stirring for 30 min to obtain a bright yellow mixed precursor solution;

[0055] 3) transferring the solution obtained in step 2) into a reaction vessel and treating at 120° C. for 24 h to obtain a yellow solid product;

[0056] 4) The yellow solid product obtained in step 3) was washed with deionized water and ethanol for multiple times, and then vacuum dried at 60° C. for 12 h to obtain an ultrathin bismuth vanadate nanosheet catalyst.

[0057] Comparative Example 3 of Example 1

[0058] An embodiment of the present invention provides a method for preparing an ultrathin bismuth vanadate nanosheet photocatalyst, which is prepared by a hydrothermal method and includes the following steps:

[0059] 1) Add 2.21 g BiCl3 into a beaker containing 60 mL of water and ethylene glycol, stir magnetically to dissolve it completely, then add 1.05 g CTAB and stir for 40 min to dissolve it completely to obtain a transparent and clear solution;

[0060] 2) adding 2.80 g of NaVO4·12H2O to the solution obtained in step 1) under stirring conditions, and magnetically stirring for 30 min to obtain a bright yellow mixed precursor solution;

[0061] 3) transferring the solution obtained in step 2) into a reaction kettle and treating at 160° C. for 3 h to obtain a yellow solid product;

[0062] 4) The yellow solid product obtained in step 3) was washed with deionized water and ethanol for multiple times, and then vacuum dried at 60° C. for 12 h to obtain an ultrathin bismuth vanadate nanosheet catalyst.

[0063] The XRD patterns of the bismuth vanadate catalysts in Example 1 and Comparative Examples 1, 2 and 3 are as follows: Figure 3 As shown in the SEM images Figure 5 , 6 and 7.

[0064] Comparative Example 4 of Example 1

[0065] An embodiment of the present invention provides a method for preparing an ultrathin bismuth vanadate nanosheet photocatalyst, which is prepared by a hydrothermal method and includes the following steps:

[0066] 1) Add 1.08 g BiCl3 into a beaker containing 60 mL of water and ethylene glycol and stir magnetically to dissolve it completely to obtain a transparent and clear solution;

[0067] 2) adding 2.80 g of NaVO4·12H2O to the solution obtained in step 1) under stirring conditions, and magnetically stirring for 30 min to obtain a bright yellow mixed precursor solution;

[0068] 3) transferring the solution obtained in step 2) into a reaction vessel and treating at 160° C. for 9 h to obtain a yellow solid product;

[0069] 4) The yellow solid product obtained in step 3) was washed with deionized water and ethanol for multiple times, and then vacuum dried at 60° C. for 12 h to obtain an ultrathin bismuth vanadate nanosheet catalyst.

[0070] Comparative Example 5 of Example 1

[0071] An embodiment of the present invention provides a method for preparing an ultrathin bismuth vanadate nanosheet photocatalyst, which is prepared by a hydrothermal method and includes the following steps:

[0072] 1) Add 1.08 g BiCl3 into a beaker containing 60 mL of water and ethylene glycol and stir magnetically to dissolve it completely to obtain a transparent and clear solution;

[0073] 2) adding 2.80 g of NaVO4·12H2O to the solution obtained in step 1) under stirring conditions, and magnetically stirring for 30 min to obtain a bright yellow mixed precursor solution;

[0074] 3) transferring the solution obtained in step 2) into a reaction kettle and treating at 160° C. for 18 h to obtain a yellow solid product;

[0075] 4) The yellow solid product obtained in step 3) was washed with deionized water and ethanol for multiple times, and then vacuum dried at 60° C. for 12 h to obtain an ultrathin bismuth vanadate nanosheet catalyst.

[0076] Example 2

[0077] like Figure 8-9 As shown, the ultrathin bismuth vanadate nanosheet catalyst was synthesized by hydrothermal treatment at 120°C for 6 h for photocatalytic degradation of oxytetracycline hydrochloride. The steps are as follows:

[0078] 1) 40 mg of ultrathin bismuth vanadate nanosheet powder prepared in Example 1 was added to a double-layer photocatalytic jacketed beaker containing 80 mL of oxytetracycline hydrochloride solution with initial concentrations of 10, 20, 40, 60 and 80 mg / L, and allowed to stand in the dark for 30 min to saturate the catalyst adsorption;

[0079] 2) Then, the mixture was placed on a magnetic stirrer at 700 rpm and a 300 W xenon lamp was used as the light source for photocatalytic experiments. 3.5 mL of the solution was taken out at intervals of 0, 5, 10, 15, 20, 25, 30, 40, 60, 80, 100 and 120 min, respectively. The solution was then separated using a 0.22 μm inorganic filter membrane. The absorbance of the obtained clarified solution was measured at a wavelength of 354 nm, and the removal rate was then calculated.

[0080] Among them, the ultrathin bismuth vanadate nanosheets of Example 2 above degrade different concentrations of oxytetracycline hydrochloride such as Figure 8 shown.

[0081] Comparative Example 1 of Example 2

[0082] Photocatalytic degradation of oxytetracycline hydrochloride by bismuth vanadate nanocatalysts was performed at 120°C for 12 h. The steps are as follows:

[0083] 1) 40 mg of bismuth vanadate nanopowder prepared in "Comparative Example 1 of Example 1" was added to a double-layer photocatalytic jacket beaker containing 80 mL of oxytetracycline hydrochloride solution with an initial concentration of 60 mg / L, and allowed to stand in the dark for 30 min to saturate the catalyst adsorption;

[0084] 2) Then, the mixture was placed on a magnetic stirrer at 700 rpm and a 300 W xenon lamp was used as the light source for photocatalytic experiments. 3.5 mL of the solution was taken out at intervals of 0, 5, 10, 15, 20, 25, 30, 40, 60, 80, 100 and 120 min, respectively. The solution was then separated using a 0.22 μm inorganic filter membrane. The absorbance of the obtained clarified solution was measured at a wavelength of 354 nm, and the removal rate was then calculated.

[0085] Comparative Example 2 of Example 2

[0086] Photocatalytic degradation of oxytetracycline hydrochloride by bismuth vanadate nanocatalysts hydrothermally at 120°C for 24h, the steps are as follows:

[0087] 1) 40 mg of bismuth vanadate nanopowder prepared in "Comparative Example 2 of Example 1" was added to a double-layer photocatalytic jacket beaker containing 80 mL of oxytetracycline hydrochloride solution with an initial concentration of 60 mg / L, and allowed to stand in the dark for 30 min to allow the catalyst to be adsorbed saturated;

[0088] 2) Then, the mixture was placed on a magnetic stirrer at 700 rpm and a 300 W xenon lamp was used as the light source for photocatalytic experiments. 3.5 mL of the solution was taken out at intervals of 0, 5, 10, 15, 20, 25, 30, 40, 60, 80, 100 and 120 min, respectively. The solution was then separated using a 0.22 μm inorganic filter membrane. The absorbance of the obtained clarified solution was measured at a wavelength of 354 nm, and the removal rate was then calculated.

[0089] Comparative Example 3 of Example 2

[0090] Photocatalytic degradation of oxytetracycline hydrochloride by bismuth vanadate nanocatalysts was performed at 160°C for 3 h. The steps are as follows:

[0091] 1) 40 mg of bismuth vanadate nanopowder prepared in "Comparative Example 3 of Example 1" was added to a double-layer photocatalytic jacket beaker containing 80 mL of oxytetracycline hydrochloride solution with an initial concentration of 60 mg / L, and allowed to stand in the dark for 30 min to allow the catalyst to be adsorbed saturated;

[0092] 2) Then, the mixture was placed on a magnetic stirrer at 700 rpm and a 300 W xenon lamp was used as the light source for photocatalytic experiments. 3.5 mL of the solution was taken out at intervals of 0, 5, 10, 15, 20, 25, 30, 40, 60, 80, 100 and 120 min, respectively. The solution was then separated using a 0.22 μm inorganic filter membrane. The absorbance of the obtained clarified solution was measured at a wavelength of 354 nm, and the removal rate was then calculated.

[0093] Comparative Example 4 of Example 2

[0094] Photocatalytic degradation of oxytetracycline hydrochloride by bismuth vanadate nanocatalyst at 160℃ for 9h, the steps are as follows:

[0095] 1) 40 mg of bismuth vanadate nanopowder prepared in "Comparative Example 4 of Example 1" was added to a double-layer photocatalytic jacket beaker containing 80 mL of oxytetracycline hydrochloride solution with an initial concentration of 60 mg / L, and allowed to stand in the dark for 30 min to saturate the catalyst adsorption;

[0096] 2) Then, the mixture was placed on a magnetic stirrer at 700 rpm / min and a 300 W xenon lamp was used as the light source for photocatalytic experiments. 3.5 mL of the solution was taken out at intervals of 0, 5, 10, 15, 20, 25, 30, 40, 60, 80, 100 and 120 min, respectively. The solution was then separated using a 0.22 μm inorganic filter membrane. The absorbance of the obtained clarified solution was measured at a wavelength of 354 nm, and the removal rate was then calculated.

[0097] Comparative Example 5 of Example 2

[0098] Photocatalytic degradation of oxytetracycline hydrochloride by bismuth vanadate nanocatalyst at 160℃ for 18h, the steps are as follows:

[0099] 1) 40 mg of bismuth vanadate nanopowder prepared in "Comparative Example 5 of Example 1" was added to a double-layer photocatalytic jacket beaker containing 80 mL of oxytetracycline hydrochloride solution with an initial concentration of 60 mg / L, and allowed to stand in the dark for 30 min to saturate the catalyst adsorption;

[0100] 2) Then, the mixture was placed on a magnetic stirrer at 700 rpm and a 300 W xenon lamp was used as the light source for photocatalytic experiments. 3.5 mL of the solution was taken out at intervals of 0, 5, 10, 15, 20, 25, 30, 40, 60, 80, 100 and 120 min, respectively. The solution was then separated using a 0.22 μm inorganic filter membrane. The absorbance of the obtained clarified solution was measured at a wavelength of 354 nm, and the removal rate was then calculated.

[0101] The degradation diagram of Example 2 and the comparative example for 60 mg / L oxytetracycline hydrochloride is as follows: Fig. 9 As shown in the figure, it can be seen that when the catalyst content is fixed, the synthesis temperature and reaction time significantly affect the catalytic effect. The ultrathin bismuth vanadate nanosheets synthesized at 120°C and 6h have the best degradation effect.

[0102] The above embodiment of the present invention provides a preparation method and application of an ultrathin bismuth vanadate nanosheet photocatalyst, which uses a hydrothermal method to synthesize the ultrathin bismuth vanadate nanosheet photocatalyst in one step. The phase is relatively pure, the method is simple, and the reaction conditions are mild. Subsequently, under stirring, a xenon lamp provides a light source to investigate the degradation of antibiotics in water under light, and the photocatalytic effect under light conditions is investigated. It is found that the morphology of bismuth vanadate catalysts synthesized by different methods significantly affects their catalytic effect. The ultrathin bismuth vanadate nanosheet photocatalyst obtained by the present invention has high performance in degrading antibiotics and can degrade a wide range of antibiotics.

[0103] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0104] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing an ultrathin bismuth vanadate nanosheet photocatalyst, characterized in that: The following steps are involved: Step 1: Preparation of ultrathin bismuth vanadate nanosheet precursor material Bismuth chloride is added into a beaker containing a certain volume of a water-ethylene glycol mixed solution, and then a certain amount of a surfactant is added into the beaker, and stirred at room temperature with a magnetic stirrer to dissolve the solution; Then, a certain amount of sodium orthovanadate dodecahydrate was added to the beaker and stirred to obtain a bright yellow mixed precursor solution; Step 2: Preparation of ultrathin bismuth vanadate nanosheet photocatalyst The bright yellow mixed precursor solution obtained in step 1 is transferred into a high-pressure reactor, and then the temperature is raised to a certain temperature in the high-pressure reactor, and the temperature is kept constant for a period of time; Finally, the ultrathin bismuth vanadate nanosheet photocatalyst was obtained by naturally cooling to room temperature, washing and drying.

2. The method for preparing the ultrathin bismuth vanadate nanosheet photocatalyst according to claim 1, characterized in that: In step 1, in the water-ethylene glycol mixed solution, the volume ratio of water to ethylene glycol is 1:1-4; The surfactant is hexadecyltrimethylammonium bromide; The molar ratio of bismuth chloride to surfactant is 1:0.4-4; The mixture was stirred with a magnetic stirrer at room temperature for 40 min to dissolve.

3. The method for preparing the ultrathin bismuth vanadate nanosheet photocatalyst according to claim 2, characterized in that: In step 1, the molar ratio of sodium orthovanadate dodecahydrate to bismuth chloride is 1:1; After stirring for 30 min, a bright yellow mixed precursor solution was obtained.

4. The method for preparing the ultrathin bismuth vanadate nanosheet photocatalyst according to any one of claims 1 to 3, characterized in that: In step 2, the treatment temperature in the high-pressure reactor is 100-200° C., and the constant temperature treatment time is 2-24 hours.

5. The method for preparing the ultrathin bismuth vanadate nanosheet photocatalyst according to claim 4, characterized in that: The treatment temperature in the high-pressure reactor is 120° C., and the constant temperature treatment time is 6 hours.

6. The method for preparing the ultrathin bismuth vanadate nanosheet photocatalyst according to claim 4, characterized in that: In step 2, the washing refers to washing the product with deionized water and ethanol for multiple times.

7. The method for preparing the ultrathin bismuth vanadate nanosheet photocatalyst according to claim 6, characterized in that: In step 2, the drying refers to vacuum drying at a temperature of 60° C. to obtain an ultrathin bismuth vanadate nanosheet photocatalyst.

8. An application of an ultrathin bismuth vanadate nanosheet photocatalyst, wherein the ultrathin bismuth vanadate nanosheet photocatalyst is prepared by the preparation method of the ultrathin bismuth vanadate nanosheet photocatalyst according to any one of claims 1 to 7, characterized in that: The application is the application of ultrathin bismuth vanadate nanosheet photocatalyst in the efficient degradation of antibiotics in water, comprising the following steps: Step a, adding a certain mass of ultrathin bismuth vanadate nanosheet photocatalyst to a certain concentration of antibiotics, and leaving it in a dark place for a period of time; Step b, then put it on a magnetic stirrer and use a 300W xenon lamp as a light source to carry out a photocatalytic experiment, take out the fixed solution at regular intervals, measure the absorbance of the upper clear liquid obtained after centrifugation, and calculate its removal rate.

9. The use of the ultrathin bismuth vanadate nanosheet photocatalyst according to claim 8, characterized in that: In step a, the time of standing in the dark is 30 minutes; The dosage of ultrathin bismuth vanadate nanosheet photocatalyst is 0 to 4 g / L; The antibiotics are one or more combinations of oxytetracycline, ceftazidime, doxorubicin hydrochloride, sulfamethoxazole, chlortetracycline hydrochloride and tetracycline hydrochloride, and the concentration of the antibiotics is 5 to 100 mg / L.

10. The use of the ultrathin bismuth vanadate nanosheet photocatalyst according to claim 9, characterized in that: In step b, a photocatalytic experiment was carried out under constant temperature conditions using a 700 rpm magnetic stirrer and a 300 W xenon lamp as a light source, the stirring time was 120 min, and the light intensity was 30-100 mW / cm 2 ; Take 3.5mL of solution at regular intervals.